Identification of Interactions between Sindbis Virus Capsid Protein and Cytoplasmic vRNA as Novel Virulence Determinants - Sokoloski, Kevin J. (PLoS Pathog, 2017)
Alphaviruses are arthropod-borne viruses that represent a significant threat to public health at a global level. While the formation of alphaviral nucleocapsid cores, consisting of cargo nucleic acid and the viral capsid protein, is an essential molecular process of infection, the precise interactions between the two partners are ill-defined. A CLIP-seq approach was used to screen for candidate sites of interaction between the viral Capsid protein and genomic RNA of Sindbis virus (SINV), a model alphavirus. The data presented in this report indicates that the SINV capsid protein binds to specific viral RNA sequences in the cytoplasm of infected cells, but its interaction with genomic RNA in mature extracellular viral particles is largely non-specific in terms of nucleotide sequence. Mutational analyses of the cytoplasmic viral RNA-capsid interaction sites revealed a functional role for capsid binding early in infection. Interaction site mutants exhibited decreased viral growth kinetics; however, this defect was not a function of decreased particle production. Rather mutation of the cytoplasmic capsid-RNA interaction sites negatively affected the functional capacity of the incoming viral genomic RNAs leading to decreased infectivity. Furthermore, cytoplasmic capsid interaction site mutants are attenuated in a murine model of neurotropic alphavirus infection. Collectively, the findings of this study indicate that the identified cytoplasmic interactions of the viral capsid protein and genomic RNA, while not essential for particle formation, are necessary for genomic RNA function early during infection. This previously unappreciated role of capsid protein during the alphaviral replication cycle also constitutes a novel virulence determinant.